An experimental study of levamisole incorporated diet on fish health and resistance against Pseudomonas aeruginosa isolated from Oreochromas niloticus - Ghada A. El-Gammal; Adel M. El-Gamal; M. A. Rashed; Amina S. Kassab; Aly S. Saif; Sabreen E. Fadl (Scientific Reports)
Abstract Pseudomonas aeruginosa (P. aeruginosa) is one of the most common ones that harm fish. P. aeruginosa has been regarded as one of the most significant threats to the fishing industry, which also affects public health. Thus, the present investigation was done in two steps; the first step was to examine the prevalence and the antibiogram of P. aeruginosa among Nile tilapia (Oreochromas niloticus (O. niloticus)) from aquaculture farms in Kafr El-shiekh Governorate with an emphasis on their antibiotic resistance genes (BlaTEM, tetA, and sul1). The second step was to investigate the effect of levamisole as a feed supplement for tilapia fish on growth performance, immunity, serum biochemistry, and the protective effect against artificial infection with the previously isolated in the first step P. aeruginosa strain. One hundred samples were collected from morbid Nile tilapia fish in the first step. The incidence of P. aeruginosa was 14%. Susceptibility of P. aeruginosa isolates to 9 antimicrobial agents showed that about half of P. aeruginosa isolates were multidrug-resistant (MDR) to (5–6) antibiotics. All of the isolates were sensitive to amikacin, ciprofloxacin, and norfloxacin (100%), and half of them were resistant to azithromycin, amoxicillin with clavulanic, tetracycline, and sulfa with trimethoprim. P. aeruginosa isolates were confirmed diagnosed using the 16S rRNA gene, which was detected in 100% of the tested isolates, and was also evaluated for the presence of antibiotic resistance genes (blaTEM, tetA, and sul1), which were 85.7%, 85.7%, and 100%, respectively. In the second step, a 2-month feeding trial was performed on 160 O. niloticus fish with a weight of 56.75 ± 3 g. Fish were randomly distributed into four groups, each at a rate of 10 fish per aquarium in four replicates, and fed on a diet containing 0.0, 500, 750, and 1000 mg levamisole/kg diet. At the end of the feeding trial, fish were challenged by pathogenic P. aeruginosa, which was isolated in the first step. The results of the in vivo trial showed that levamisole safely improved the growth and immunity of Nile tilapia without side effects on liver function.